ION Orchard: atmosphere and consumption in Singapore. (August 2015) - Hudson, Chris
Every major shopping mall in Singapore is pervaded by atmospheres designed to attract consumers, but recent innovations in the production of atmosphere at ION Orchard make it a key site for the examination of the link between atmospheres and consumption. If a shopping mall is to distinguish itself from the many other shopping spaces in a city with such a proliferation of malls as Singapore, it needs to offer more than just shopping. It must provide the possibility for novel forms of embodied sensory experiences and the constant reinvention of excitement. In Singapore the instrumental generation of atmospheres of excitement is also practised on a national scale. This article examines the production of atmosphere in ION Orchard – one of Singapore's newest and most spectacular malls. It places the discussion in the context of government-directed attempts to universalize sensory manipulation and create a more general sense of affective atmosphere in the nation-state.